2019
DOI: 10.1002/jclp.22848
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a web‐based Acceptance and Commitment Therapy (ACT) program to promote mental health in university students

Abstract: Objective: This study evaluated a 4-week web-based Acceptance and Commitment Therapy (ACT) mental health promotion intervention for university students.Method: Participants were randomized to intervention (n = 596) or waitlist control (n = 566). Assessment of primary outcomes (depression, anxiety, stress, well-being, selfcompassion, life satisfaction, and academic performance) and ACT processes (acceptance, cognitive fusion, education values, valued living, and present moment awareness) occurred at pre-and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(145 citation statements)
references
References 62 publications
4
141
0
Order By: Relevance
“…Ironically, telepsychological approaches such as wearable devices may actually be more appealing to people holding negative views toward psychological treatment and who have less experience in help‐seeking (Hunkin, King, & Zajac, 2020). Other extremely promising web‐based approaches that have the potential to reach individuals not entering traditional treatment, or as a supplement to traditional treatment, are showcased in this special issue, including Acceptance and Commitment therapy for college students (Viskovich & Pakenham, 2020), an avatar‐based intervention for military family caregivers (Wilcox, 2020), and a self‐management positive psychology intervention (Görges, Oehler, von Hirschhausen, Hegerl, & Rummel‐Kluge, 2020). As Heesacker et al (2020) note, web‐based interventions such as these are showing respectable levels of feasibility and efficacy, although treatment computerization represents an extension of traditional mental health care providers, not a replacement.…”
Section: Telepsychology Special Issuementioning
confidence: 99%
“…Ironically, telepsychological approaches such as wearable devices may actually be more appealing to people holding negative views toward psychological treatment and who have less experience in help‐seeking (Hunkin, King, & Zajac, 2020). Other extremely promising web‐based approaches that have the potential to reach individuals not entering traditional treatment, or as a supplement to traditional treatment, are showcased in this special issue, including Acceptance and Commitment therapy for college students (Viskovich & Pakenham, 2020), an avatar‐based intervention for military family caregivers (Wilcox, 2020), and a self‐management positive psychology intervention (Görges, Oehler, von Hirschhausen, Hegerl, & Rummel‐Kluge, 2020). As Heesacker et al (2020) note, web‐based interventions such as these are showing respectable levels of feasibility and efficacy, although treatment computerization represents an extension of traditional mental health care providers, not a replacement.…”
Section: Telepsychology Special Issuementioning
confidence: 99%
“…The eight papers in this section address common concerns that often accompany clinical psychology. The randomized controlled trial of a web‐based application of Acceptance and Commitment Therapy (Hayes, Strosahl, & Wilson, 2011) for college students extends the evidence base for this approach (Viskovich & Pakenham, 2020). It also demonstrates how university counseling centers can offer evidence‐based treatments to students using telepsychology.…”
Section: Clinical Practicementioning
confidence: 99%
“…Research has investigated the use of web-based ACT interventions to increase education values in university students, and their subsequent effects on academic and mental health outcomes. These studies have reported increases in participants' education values from pre-to post-intervention (Levin et al, 2015;Levin et al, 2014;Viskovich & Pakenham, 2018a, 2018b. Furthermore, these increases were maintained at 3-week (Levin et al, 2014) and 3-month follow-ups (Viskovich & Pakenham, 2018b).…”
Section: Education Valuesmentioning
confidence: 95%
“…Values and committed action processes are taught through experiential exercises that are designed to facilitate values clarification, goal setting, and the development of strategies to act on chosen targets. Commonly used exercises in web-based interventions are the values card sort (Levin, Hayes, et al, 2016;Levin et al, 2014;Viskovich & Pakenham, 2018a, 2018b; and the setting of specific, measureable, attainable, realistic and time-oriented (SMART) goals (Chase et al, 2013;Paliliunas et al, 2018;Viskovich & Pakenham, 2018a, 2018b. The 80 th…”
Section: Values and Committed Actionmentioning
confidence: 99%
See 1 more Smart Citation